ANALISIS SISTEM PEMUNGUTAN, PEMBAYARAN, PENCATATAN DAN PELAPORAN PAJAK MINERAL BUKAN LOGAM DAN BATUAN PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN PULAU MOROTAI - Mahino, Yosceline; Karamoy, Herman; Pusung, Rudy J. (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
One of the efforts made in national development is the implementation of autonomy area. With regional autonomy, an autonomous region must be able to take care of and arrange the financing of the area itself. In order to implement the sector policy which plays an important role in regional financing is local revenue. Original regional income that sourced from tax revenue, levies and other legitimate regional revenues. Local Tax is one source of local revenue potentials that can be developed throught local tax revenues. Morotai Island Regency is one of autonomous district that has large potential resources, one of which is non-metallic minerals and rocks tax, but have not been managed effectively. The purpose of this study is to analyze whether the collection system, payment, recording and reporting of Non Mettalic mineral and Rocks tax already in accordance with Undang-Undang No 28 Tahun 2009 and Peraturan Pemerintah Nomor 55 Tahun 2016. The analytical method used is descriptive method. Based on the results of the study, it can be concluded that collection system, payment, recording and reporting of Non Mettalic mineral and Rocks tax is already appropriate with Undang-Undang No 28 Tahun 2009 and Peraturan Pemerintah Nomor 55 Tahun 2016 but in BPKAD still not a Standar Operation Procedur (SOP) for tax revenue. Internal Control for Non Metallic Mineral and Rocks tax using analysis COSO are sufficient only to needan increase in the risk assessment component.Keywords: Non Mettalic Mineral and Rocks Tax, Collections System, Payment, Recording, Reporting, Internal Control